1992
DOI: 10.1002/j.1552-4604.1992.tb03792.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamic and Pharmacokinetic Evaluation of a New Transdermal Delivery System with a Time‐Dependent Release of Glyceryl Trinitrate

Abstract: The pharmacokinetics of glyceryl trinitrate (GTN) and its main metabolites as well as the hemodynamic effects of a new transdermal delivery system (TDS) were investigated in ten healthy male volunteers using a single blind, placebo-controlled study design with an application period of active drug of 4 successive days. The adhesive-type matrix system contains 20-mg GTN and released about 75% in a time-dependent manner. The plasma concentrations of GTN and its metabolites 1-2- and 1-3 glyceryl dinitrate reflecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Nitroglycerin in therapeutic sublingual, spray, ointment, and transdermal patch doses increased the a/b ratio from 26 to 89%. 14,16,18,[25][26][27][28][29][30][31] Chowienczyk et al 14 found the highest peak increase of the a/b ratio, 205% in an adult receiving nitroglycerin, 0.1 mg IV, and 124% in an adult receiving albuterol, 20 g/min IV. Since changes of the a/b ratio from the action of NO follow a dose-response curve, whole-body, periodic acceleration appears to be much more potent in accessibility to NO than organic nitrates or ␤-adrenergic agonists in terms of vasodilatation of the resistance vessels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitroglycerin in therapeutic sublingual, spray, ointment, and transdermal patch doses increased the a/b ratio from 26 to 89%. 14,16,18,[25][26][27][28][29][30][31] Chowienczyk et al 14 found the highest peak increase of the a/b ratio, 205% in an adult receiving nitroglycerin, 0.1 mg IV, and 124% in an adult receiving albuterol, 20 g/min IV. Since changes of the a/b ratio from the action of NO follow a dose-response curve, whole-body, periodic acceleration appears to be much more potent in accessibility to NO than organic nitrates or ␤-adrenergic agonists in terms of vasodilatation of the resistance vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Similar falls in the dicrotic notch occur with therapeutic doses of organic nitrates. 16,18,24,35 Dicrotic notch position changes contrast with serum nitrite levels measured after interventions designed to increase or decrease NO release. Here, infusions of nitrite in volunteers to reproduce the serum changes for this metabolite of NO fail to effect vasodilatation as measured by forearm blood flow measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, an intermittent dosage regimen, typically where the patch is removed at night, has been recommended (Physicians Desk Reference 1992). Wiegand et al (1992) recently reported that a 8-to 12-hour period of nitroglycerin withdrawal restored the full efficacy of the drug.…”
Section: Tolerancementioning
confidence: 98%
“…The digital pulse throughout the study was recorded at the same distal phalanx using a photo electric sensor (Hellige AG, Freiburg, FRG), and the signal was amplified by an ECG-recorder (Hellige Cardiognost EK 413, Hellige AG, Freiburg, Germany). At least 20 pulse waves were recorded during each measurement and the a/b ratio was calculated, where a is the height of the systolic peak and b the high of the dicrotic wave (Imhof et al 1980;Wagner et al 1990;Wiegand 1991;1992). Ten consecutive waves were evaluated and the a/b ratios were averaged.…”
Section: Haemodynamic Measurementsmentioning
confidence: 99%